2015
DOI: 10.1371/journal.pone.0115240
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Water Content and Temperature on the Degradation of Cry1Ac Protein in Leaves and Buds of Bt Cotton in the Soil

Abstract: Determining the influence of soil environmental factors on degradation of Cry1Ac protein from Bt cotton residues is vital for assessing the ecological risks of this commercialized transgenic crop. In this study, the degradation of Cry1Ac protein in leaves and in buds of Bt cotton in soil was evaluated under different soil water content and temperature settings in the laboratory. An exponential model and a shift-log model were used to fit the degradation dynamics of Cry1Ac protein and estimate the DT50 and DT90… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 37 publications
3
16
0
Order By: Relevance
“…A.1A) compared with the range of 0.5-11.4°C, 0.2-11.3°C and 7.7-15.4°C at the three sites in our previous study (Xiao et al, 2014), which may have led to the increased level of k c . These results confirm the effects of temperature and water content on the degradation of the Cry1Ab protein released from the Bt crop residue in field soil, similar to the laboratory results presented by Feng et al (2011) and Zhang et al (2015).We found that k c derived from both conditions was positively correlated with the initial concentration of the Cry1Ac protein in rice residues. This finding was supported by Wang et al (2007) who revealed that k c decreased as the concentration of purified Cry1Ab protein in aqueous solutions declined.…”
Section: Cry1ac Protein Degradationsupporting
confidence: 90%
See 3 more Smart Citations
“…A.1A) compared with the range of 0.5-11.4°C, 0.2-11.3°C and 7.7-15.4°C at the three sites in our previous study (Xiao et al, 2014), which may have led to the increased level of k c . These results confirm the effects of temperature and water content on the degradation of the Cry1Ab protein released from the Bt crop residue in field soil, similar to the laboratory results presented by Feng et al (2011) and Zhang et al (2015).We found that k c derived from both conditions was positively correlated with the initial concentration of the Cry1Ac protein in rice residues. This finding was supported by Wang et al (2007) who revealed that k c decreased as the concentration of purified Cry1Ab protein in aqueous solutions declined.…”
Section: Cry1ac Protein Degradationsupporting
confidence: 90%
“…In the current study, the decay of the Cry1Ac protein was well described using a first-order kinetics model, which is consistent with previous studies (e.g., Wang et al, 2006b;Xiao et al, 2014;Zhang et al, 2015). Furthermore, the degradation of the Bt protein in rice residue did vary with water management practices in the field as hypothesized.…”
Section: Cry1ac Protein Degradationsupporting
confidence: 90%
See 2 more Smart Citations
“…Moreover, there were no significant differences in the detectability of both tests when saliva samples were incubated in dried-soil (37°C, 0-72 h). These results suggest that environmental microbial effects (e.g., protein degradation) require environmental humidity (18,23).…”
Section: Comparison Of Qualitative Saliva Testsmentioning
confidence: 92%